Evaluation of saline tolerance at the seedling stage of various maize cross combinations - Huu Hung Nguyen; Van Vang Luong; Thi Minh Tam Ngo; Hoai Son Vu; Xuan Thang Nguyen (Vietnam Journal of Science, Technology and Engineering, 2017)
This study was conducted at the Maize Research Institute of Vietnam using 24 maize hybrids, identified as STM1 to STM24, at five different salt concentrations, which were 0, 50, 100, 150, and 200 mM NaCl. After seven days of germination at room temperature, seedlings were transplanted to nutrient-rich solutions salinized with salt. 17 day-old seedlings were then harvested to calculate their growth parameters of the day to seedlings fully wilt and degradation, root and shoot length, seedling dry matter production, and content. As the study results show, salt stress caused the reduction of plant growth in all hybrids, however, the STM10 and STM21 varieties showed the best salt tolerance, while STM17 and STM18 presented most salt-sensitive. The analyzed results for Na+ and K+ showed that among the hybrids, STM21 had lower Na+ and higher K+ contents in both roots and shoots of the seedlings than others.